Identification of a de novo ANK1 mutation in a Chinese family with hereditary spherocytosis. Issue 6 (3rd July 2018) - Guan, Hongzai; Liang, Xinping; Zhang, Rong; Wang, Haiyan; Liu, Wenmiao; Zhang, Ru; Yang, Jie; Liu, Shiguo
ABSTRACT: Objectives: Hereditary spherocytosis (HS) is a genetic heterogeneous disorder characterized by sphere-shaped erythrocytes on peripheral blood smear with a few clinical manifestations. As an important red cell membrane protein, ankyrin 1 can interact with transmembrane proteins and the membrane skeleton and mutations in the ankyrin 1 ( ANK1 ) genes affect about half of all patients with HS. The purpose of this study was to investigate a Chinese Han family with HS to find out the causative gene mutation and explore the genotype–phenotype correlation which can provide the basis for the pathogenesis and prenatal diagnosis for this disease. Methods: Whole exome sequencing (WES) followed by Sanger sequencing was performed on subjects with HS from a Chinese family in Shandong Province. Results: A de novo nonsense ANK1 mutation (c.796G > T, p.Glu266X), a single-nucleotide change from G to T which caused a substitution from glutamic acid to an immature stop codon at codon 266, was identified. Discussion: Our finding suggested that a de novo nonsense mutation in ANK1 may be causative to HS which plays an important role in supplementing the mutational spectrum of the ANK1 and explaining the mechanism of HS. Our study also indicated that WES can be an effective and accurate diagnostic tool in the discovery of causative mutations in genetic heterogeneous Mendelian disorders.